KONSEPSI HARTA BENDA DALAM PERKAWINAN: CONCEPTION OF PROPERTY IN MARRIAGE - Elmi, M (Mitsaqan Ghalizan, 2022)
Overcoming property related to marriage is a discussion that has always been interesting from time to time. The concept of joint property, inherited property or what is often referred to as gono-gono-equity property is a phenomenon that seems to have no end. Islamic law is here to provide a universal concept to be implemented in the concept of property in books. This research is a normative legal research based on literature review by reviewing the literature that discusses the concept of property in marriage. The results of this study indicate that Gono gini in Islam actually does not exist. However, with the existing phenomena, Islam is still able to answer the law of joint property or what we know as gonogyny. Islam still allows the existence of joint property. In fact, Islam allows ta'lik before marriage to facilitate the distribution of joint assets if separation occurs later. Wealth must be utilized as best as possible while still paying attention to Islamic rules. In disputes, assets are used to meet family needs for the benefit of all family members. If the assets are more then our reward is donating or donating to third parties